(untitled) (MAUSAM, 1996)
The shelterbelt influence on the microclimate of gram crop in different intercropping systems comprising of four treatment, viz., pure gram, 1 : 1, 2 : 1 and 4 : 1 gram and raya, was quantified. Albedo varied from 14.8 to 22.6 percent in various treatments with highest value fo 18.3 percent in pure gram treatment, whereas, photosynthetically active radiation absorption was highest in 2 : 1 gram treatment (76%). Maximum reduction (69.2 per cent) in wind speed was observed in 1 : 1 intercropping system at 4h distance from the edge of the shelterbelt in comparison to pure gram field. Relative humidity was 8 to 15 percent less in the sheltered gram as compare to the pure gram, whereas, the average air temperature increased by 1 to 2 C in the sheltered crop over that of the pure gram and this increase was in the range of 9.9 to 12.2 per cent at 4h distance from the edge of shelterbelt. The grass minimum temperature was higher by 0.7degree cent grate in 2 : 1 treatment over that of pure gram during the months of January and February.